MENINGKATKAN KEMAMPUAN SISWA KELAS XII IPS 3 MAN 2 BOJONEGORO MENULIS KALIMAT PASSIVE VOICE MELALUI MODEL PEMBELAJARAN MAKE A MATCH TAHUN PELAJARAN 2022/2023 - Happy Chirma Sya’Roni (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The aim to be achieved in this research is to determine the use of the Make a Match Learning Model in improving students' ability to write passive voice sentences in Class XII IPS 3 MAN 2 Bojonegoro. This classroom action research was carried out at MAN 2 Bojonegoro. This research was carried out from January to February 2023 or in the even semester of the 2022/2023 academic year. The subjects in this research were all students of class XII IPS 3 MAN 2 Bojonegoro for the 2022/2023 academic year, totaling 26 students as research subjects. Based on the results of the research conducted, it can be concluded that improving students' ability to write Passive voice sentences in English subjects using the make a match learning model can improve the learning outcomes of class XII IPS 3 students in the even semester of the 2022/2023 academic year at MAN 2 Bojonegoro. This is shown in the average score of student learning completeness in the pre-cycle which was obtained at 53.85% and increased in the first cycle to 69.23%. Continues to increase in cycle II to 92.31%. Meanwhile, for student activities, in cycle I the average percentage value was 59% and increased to 91% in cycle II.